Simulacion numérica del campo de velocidades, presión y temperatura de flujo de jugo de caña en un evaporador Roberts - Villarreal Albitres, William Fernando (2013)
In the sugar industry, evaporators play an important role in the crystallization process of crystal sugar and heat economy. In this thesis two main objectives are intended to achieve it. The first objective was to determine the behavior of the field of velocities, temperatures and pressures of cane juice, of a two-phases system of a evaporator Roberts. The second objective was to determine the effect of inlet design on the juice to the evaporator heat transfer coefficient. As a study object was defined both the cane juice and Roberts evaporator. In order to computationally simulate the motion of a particle of sugarcane juice in a two-phase, CFX-ANSYS code was used, which calculates the flow field by the Finite Volume Method. Roberts evaporator of 1050 m2 in Industrial Pucalá in Lambayeque was used, which conditions of both cane juice and vapor was recorded flow. To determine the effect of the juice supply system on the heat transfer coefficient; three evaporators of 700 m2, 845 m2, and 1134 m2, respectively, were used. To validate the temperature field profile computationally simulated, boiling juice experimental data were measured by placing temperature sensors above and below the evaporator calandria. Computational results obtained from computer simulation of the velocity, temperature and pressure fields of cane juice of an evaporator Roberts showed that the juice velocity drops dramatically at the bottom of the calandria. Abundant juice recirculation occurs between the outlet pipe of juice evaporated and the down take of recirculation. Regarding the temperature profile, the fluid reaches the highest temperatures in the middle of the height of the calandria and pressure decreases uniformly from the bottom to the body of the evaporator. Concerning the position and distribution of the juice into the evaporator, the results indicated that the juice temperature is influenced by the juice distributor. Eccentric juice distributors to the central axis of the evaporator have the highest heat transfer coefficient. The values of the temperature field both simulated computationally as those measured experimentally shown to be in good agreement, validating the computational model developed in this thesis.